2021
DOI: 10.3390/agronomy11112156
|View full text |Cite
|
Sign up to set email alerts
|

Response of Crops to Conservation Tillage and Nitrogen Fertilization under Different Agroecological Conditions

Abstract: Effects of soil tillage (CTconventional, SS-subsoiling, CH-chiselling, DH-disk-harrowing and NT-no-till) and nitrogen rate (reduced N1, optimal N2 and luxury N3) on yield and yield components of maize and winter wheat in two different agricultural subregions of Croatia (Magadenovac and Cacinci site), were studied in the years 2013–2014 as part of a long-term experiment. Maize yield and yield components were influenced by site properties, tillage and nitrogen treatments. The highest yields and yield components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The positive and significant correlations in the cereal yields and similar spatial distribution of the crop yields were discussed [29]. Maize yield was influenced by site properties, tillage, and nitrogen treatments [9]. This paper highlighted the rainfall amounts in the critical period (May).…”
Section: Relationship Of All Variables and Maize Yieldsmentioning
confidence: 76%
See 1 more Smart Citation
“…The positive and significant correlations in the cereal yields and similar spatial distribution of the crop yields were discussed [29]. Maize yield was influenced by site properties, tillage, and nitrogen treatments [9]. This paper highlighted the rainfall amounts in the critical period (May).…”
Section: Relationship Of All Variables and Maize Yieldsmentioning
confidence: 76%
“…Maize is highly sensitive to environmental conditions, especially to abiotic factors such as rainfall, available soil moisture, air and soil temperature, soil type, etc. [9]. The variability of the physical, chemical, and biological properties of the soil is the major factor for the diversity in crop production [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tillage practices also influence the yield of various crops. Although with varied influence across locations, tillage affects the structure of the soil, which in turn affects the capacity for water and nutrient conservation (Jug et al., 2021). On the contrary, barriers to yield increase emanate from suboptimal input use and a lack of improved technologies (Assefa et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has a significant impact on biological activity of the soil and on the possibility of ensuring conditions for the proper growth and development of crops (Piotrowska and Wilczewski, 2020;Souza et al, 2021). Penetration resistance (PR) is especially important as it is a result of soil water content and bulk density (Lardy et al, 2022) which are largely influenced by both tillage systems and field traffic (Jug et al, 2021;Wang et al, 2022). Since measurements of PR are relatively rapid, they are suitable for the evaluation of the mechanical impedance to root elongation (Colombi et al, 2018;Gliński and Lipiec, 2018) and the effects of tillage on pore and aggregate structure (Dexter et al, 2007, Alaoui et al, 2011, the size of the structural units and also the structural discontinuities in the soil profile (Whalley et al, 2000;Lowery and Morrison, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These physical properties of soil are substantially influenced by shifting from conventional (intensive) tillage coupled with monocropping and the partial recycling of crop residues to conservation tillage systems including practices involving minimized soil disturbance, permanent soil cover with crop residues and diversified crop rotation (Powlson et al, 2016;Gonzalez-Sanchez et al, 2019;Devkota et al, 2022;Du et al, 2022). These practices are the main components of conservation agriculture (CA) (Ranaivoson, 2017;Xiao, 2021;Francaviglia et al, 2023) which has been shown to be suitable for improving soil structure and organic carbon sequestration (Kocira et al, 2020;Hussain, 2021;Mia et al, 2023), soil moisture conservation and in the reduction of erosion (Kocira et al, 2020;Mia et al, 2023), thereby sustaining soil health and reducing soil degradation (Kocira et al, 2020;Jug et al, 2021;Jayaraman and Dalal, 2022) and also lowering the input costs of crop production (Busari et al, 2015;Smith et al, 2021;Musto et al, 2023). Therefore, in recent years, CA has been promoted as an alternative to conventional agriculture in many parts of the world (Jug et al, 2019;Hussain et al, 2021;Hessel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%